Plantear una reforma legal a la ley de compañías a fin de que guarde armonía con la constitución de la república del Ecuador. - Cabezas Baño, Narcisa Elizabeth (2015)
The company was created to associate several capiales that are scattered which are insufficient to constitute a business for which a large amount of investment is required, whereby humans are associated, and then bind its capital obtain economic I redito. Corporate law has undergone rapid evolution in the West dates back to Rome, where societies were as entities that allowed individuals to organize and carry out various activities, but enjoy them in conducting a legal personality or a limitation liability, for unlimited responded with personal wealth of social obligations. Later, in the industrial revolution it became necessary to universalize the benefit of the limitation of liability, which until that time favored only certain privileged groups, it was able to establish one of the characteristic elements of the current corporate law which led to a varied number of different social types. Just as the world began to have a very important development in our country in the Early Republican Period, incipient economic development was therefore rather an era of political instability lived; is pr do that on November 4, 1831, just one year having gained independence, the Constitutional State Congress authorized the executive to adopt and become effective code Spanish trade, which contained some regulations concerning commercial companies. In 1875, entered into force the new Commercial Code, commissioned by the National Congress to the Supreme Court. In 1906, as a result of the new Constitution of Alfaro's new Code of Commerce, which was taken as a basis of governing in Venezuela since 1903, The Actual Commercial Code was issued in 1960, dictates that along the years suffered some mutilation of certain legal institutions became part of independent legal bodies, such as check law, insurance law and related commercial companies since 1964 takes effect the First company Law in our country. The first Companies Act in which it began to clear and precise standards for companies, the regulations previously established the Commercial Code delegated many of these rules the status of each company which turned out to be greater discretion Societies of the time, the Companies Act then began to regulate issues such as: The obligation of the Public Limited Companies Trade submitted to the newly created Superintendency of Corporations (forerunner of today's Superintendency of Companies) a report in January of each year on the results obtained the previous year Companies. That the Public Limited Companies of the time should have at least 5 shareholders to survive. The minimum requirements that must have share certificates is established. Called stub books, required documents within the corporate books of a public limited company is created. However at present and several constitutional changes, we note that the company law does not resemble the current constitutional reality, so I have thought proper to present work by RAISE A LEGAL REFORM ACT OF COMPANIES IN ORDER TO SAVE HARMONY WITH THE CONSTITUTION OF THE REPUBLIC OF ECUADOR